Avaliação educacional diagnóstica do talento de liderança: estudo de caso em uma escola estadual de educação profissional do Ceará - Salgado, Paulo Sérgio Bessa (2018)
There is 25% of talented people distributed in the whole world population, which indicates the participation of hereditary factors. However, without environment stimulation, no talent develops. The education of talented students is justified based on a personal point of view, since each individual has the right to the full development of his/her potential, as well as based on a social point of view, towards a socially productive use of those capacities. Regarding leadership talent, schools must encourage it to the exercise of citizenship. Moscovici (2015); Renzulli (1984, 1986), Luckesi (2005), Viana (2005), Gardner (1995), proposed a theoretical framework to this study. They point out the importance of the participation of educators and students in the process of identification and development of talents. The main purpose of the current research was to accomplish an investigation about the practice of identification of the leadership talent carried out with the students who occupy the official position of classroom leaders, from the 1st to 3rd year of High School at a technical-professional school in Ceará-Brazil. Specifically, this study aimed: i) verifying what type of diagnostic educational evaluation is used to identify students indicated as classroom leaders; ii) identifying the characteristics of the leadership talent presented by these students; iii) gathering suggestions, with both teachers and students, for improvement of the identification and teaching strategies of these students. Thus, a qualitative research was accomplished, as a case study. The mixed questionnaire and the focus group were used as instruments for data collection. A content analysis of the collected data was accomplished. The samples were composed by: i) 8 students, ii) 10 teachers and iii) 8 managers; 26 subjects altogether. The results revealed that the type of diagnostic educational evaluation of leadership talent used by educators is classificatory, without the use of better techniques to identify characteristics, postures and skills needed to be a classroom leader. The current leaders present a democratic, proactive and server style. The main characteristics identified were responsibility, commitment and exemplary posture. The subjects consulted suggested training on leadership and partnerships to improve the selection process and the teaching practices for this population.